Well-being as a Collective Atmosphere (Lebenswelt. Aesthetics and philosophy of experience., 2019)
A neo-phenomenological and atmospherological approach, mainly based on a first-person perspective, seems perfectly entitled to consider subjective and collective well-being as the starting point for a (non-quantitative) philosophical reflection. The question is, however, whether and how well-being, also as an atmosphere, can be really investigated and verified. The paper examines many traditional roblems hindering the research (difficulty in investigating it directly, degree of extent, intensity, comparison-dependence, temporal development, consistency, and continuity) and suggests to analyze well-being from a pathic-atmospheric point of view. It therefore focuses especially on the idea of “flow”, wonders how much our well-being depends on the felt-bodily resonances triggered by atmospheric situations, considers the probable parallels between the aesthetic-phenomenologic notion of “atmosphere” and the sociological one of “climate”, finally, underlines the (also political) need of an atmospheric competence that is able to partly immunize against today’s widespread manipulative atmospherization.
Keywords: well-being; atmospheres; felt-bodily resonances; flow; atmospheric competence